Uji Coba Teknik Penilaian Kinerja Karyawan Menggunakan Metode Behaviour Anchor Rating Scale di PT X - Nabila Agustina; Desta Melani Amalia; Syamsul Hidayat (Master Manajemen, 2025)
Employee performance appraisal is an important part of the human resource management process in the company and decision support in employee performance appraisal ensures that the assessment results are objective and not influenced by subjective factors. So that the urgency of research on determining decision support models in employee performance appraisal based on the skills or abilities possessed by each employee. In this study applying the Behavior Anchor Rating Scale (BARS) method is used to assist decision makers in determining the final value of ranking the best alternatives. This research aims to be able to apply the BARS method in supporting employee performance appraisals, with decision support techniques that can help decision makers make decisions objectively. Based on the results of the performance assessment with the BARS method, the researcher found the actual average score results. The researcher obtained data on Discipline with a score of 4.5, Skill with a score of 3, Responsibility with a score of 3.6 and Teamwork with a score of 1.2. Of the four factors that are of small value, namely communication between employees, the results of the researcher's analysis when there is no approach between employees and each other.